MULTIPLE EXPOSURE DAN DIGITAL IMAGING SEBAGAI METODE PEMBUATAN PHOTOBOOK BAHASA ISYARAT - Susanti, Kristina Novi; Asran, Diana Safinda; Prakoso, Priaji Iman (Institut Seni Indoensia Surakarta, 2023)
This study explores photographic works that can be utilised as fine artwork and as learning media for deaf people. The research method used in creating works of art is searching for ideas, deepening and developing them. Through this method, the creation of photography works bg visualizing hand movement and expressions using two techniques, namely multiple exposure and digital imaging. The object of this photo is someone who has mastered sign language. This research then produced several photographic works combined into a photobook that can be used as a teaching and learning media for teachers and students at special schools.Keywords: photography, sign language, photobook, learning media.